Involvement of Neuroactive Steroids in Pain, Depression and Anxiety - ARICIOĞLU, FEYZA (KARGER, 2015)
Comorbidity between major depressive disorder (MDD), anxiety (generalized anxiety, panic disorder, social anxiety disorder) and pain is a major complicating factor in the diagnosis and treatment of psychiatric and neurological disorders. Although numerous neurotransmitters and/or neuromodulators may be involved, abnormalities in the GABAergic and glutamatergic systems seem to be a common factor in all these disorders. Neuroactive steroids (NASs) have been the object of considerable interest in this area in recent years since they appear to act predominantly on GABA-A and glutamate NMDA receptors. An overview of the possible involvement of NASs in MDD, anxiety and pain is provided in this chapter. (C) 2015 S. Karger AG, Basel
Keywords: NEUROPATHIC PAIN; SPINAL-CORD; GLUTAMATE TRANSPORTERS; GABA(A) RECEPTORS; GENE-EXPRESSION; DISORDERS; PROGESTERONE; RATS; NEUROSTEROIDS; INHIBITION